Using social networks sites in the purchasing decision process - Miranda, F.; Rubio, S.; Chamorro, A.; Loureiro, S. M. C. (International Journal of E-Business Research, 2014)
The rise of Web 2.0 tools and mobile devices means that the image of the traditional consumer has to be replaced with an active, permanently connected, consumer who uses the Internet to find information about brands and to share opinions and shopping experiences with other consumers – a consumer who can be classified as a prosumer (producer + consumer). In this context it is important for marketers to know how consumers use social networks within their purchasing decision process. The present work describes an online survey of more than 500 Facebook users in Spain and Portugal, aimed at identifying which aspects most influence their intention to use this social network in their purchasing decisions. A structural equation model was constructed based on the Technology Acceptance Model (TAM), in which the intended use of Facebook in purchasing decisions depends on two variables: perceived usefulness and perceived ease of use, with attitude being a mediating variable. The background variables considered were aptitude, network externalities, perceived privacy protection, and social influence. The results show that the intended use of Facebook in purchasing decisions is influenced by its perceived usefulness, by social influence, and by the attitude to Facebook. In contrast, the perceived ease of use does not have such direct influence.